The Influence of Fermentation Conditions on The Antioxidant and Physico-Chemical of Arabica Coffee from Kerinci Region of Indonesia - Nizori, Addion; Jayanti, Elkanah; Surhaini, Surhaini; Gusriani, Ika; Mursyid, Mursyid; Purba, Daniel Tua (Indonesian Food Science and Technology Journal, 2021)
Abstract—Coffee quality can depend on several factors such as the species/varieties cultivated, the processing after the harvesting phase, geographical origin, and climatic factors. Fermentation is one of the post harvest technology that influence coffee chemical and sensory properties. This study was to determine the effect of fermentation time into antioxidant and physicochemical of Arabica coffee from Kerinci region Indonesia. Research design used was randomized complete design with 5 combinations of treatments, which are 12, 20, 28, 36, and 44 hours fermentation with 3 replicates. The results shows fermentation time have a significant effects on moisture content, pH, antioxidant activity. The duration of fermentation results in increasing higher moisture content, lower pH value and decreased antioxidants. Keywords— Anaerobic fermentation, coffee processing, antioxidan